Tunable Porosities and Shapes of Fullerene‐Like Spheres. Issue 16 (11th March 2015) - Dielmann, Fabian; Fleischmann, Matthias; Heindl, Claudia; Peresypkina, Eugenia V.; Virovets, Alexander V.; Gschwind, Ruth M.; Scheer, Manfred
Abstract The formation of reversible switchable nanostructures monitored by solution and solid‐state methods is still a challenge in supramolecular chemistry. By a comprehensive solid state and solution study we demonstrate the potential of the fivefold symmetrical building block of pentaphosphaferrocene in combination with CuI halides to switch between spheres of different porosity and shape. With increasing amount of CuX, the structures of the formed supramolecules change from incomplete to complete spherically shaped fullerene‐like assemblies possessing an Ih‐C80 topology at one side and to a tetrahedral‐structured aggregate at the other. In the solid state, the formed nano‐sized aggregates reach an outer diameter of 3.14 and 3.56 nm, respectively. This feature is used to reversibly encapsulate and release guest molecules in solution.